Ferromagnetic Resonance Characterization of Nano-FePt by Electron Spin Resonance - S. S. Nkosi; H. M. Gavi; D. E. Motaung; J. Keartland; E. Sideras-Haddad; A. Forbes; B. W. Mwakikunga (Journal of Spectroscopy)
Electron spin resonance (ESR) measurements at room temperature and X-band microwave frequency were performed on highly crystalline FePt system thin films. Fairly high DC static magnetic field absorption of about 300 mT was observed in these films. We attribute the high field absorption to ferromagnetic resonance (FMR). Upon increasing iron content in FePt system, no detectable spin waves modes were identified already at room temperature. This signifies a homogeneous distribution of the magnetization across the films. We qualitatively attributed such homogeneity distribution in the films to self-assembly of these Fe–Pt system nanoparticles. The results revealed that the FePt system contains hyperfine coupling with sextet I=5/2 exhibiting a phase reversal behaviour compared to FMR line. Both iron content and crystallite size increased the FMR intensity making the films good candidates for large data storage mediums and spintronics.